Multi-scale pore structure characteristics and main controlling factors analysis of Longtan formation shale in Northwest Guizhou - Huang, Yuqi; Zhang, Jinchuan; Zhang, Peng; Tang, Xuan; Yang, Junwei (Frontiers in Earth Science, 2023)
Marine-continental transitional shale strata are widely distributed in China and have high gas potential. The Longtan shales are a typical marine-continental transitional coal-bearing shale system in Northwest Guizhou. Low-temperature N2 adsorption experiments and high-pressure mercury injection experiments were carried out on the unweathered shale samples from Well JS-1. The multi-scale fractal dimensions were calculated based on the MESP (Menger-sponge) model, MESA (mercury saturation) model, and FHH (Frenkel-Halsey-Hill) model respectively. The macropores (≥100 nm) are mainly inorganic with a fractal dimension D1 between 2.8628–3.2057, indicating the macropore structure is relatively complex. The proportion of the macropores in total pores is not high in comparison to mini-micropores (<50 nm), and the content of brittle minerals and pyrite mainly controls its structure. Among the mesopores (50–100 nm), inorganic pores are still the primary pore type, but the proportion of organic pores increases. The fractal dimension D2 is between 2.2125–2.3016. It has medium complexity, and the proportion in the total pores is slightly higher than that of macropores. The influence of organic matter abundance on mesopore structure is greater than that in macropore because of the increase in the proportion of organic pores, making the controlling mechanism of mesopore structure more complicated. Mini-micro pores are mainly organic pores. The fractal dimension D3 (fractal dimension of mini-micropores under low relative pressure, P/P0 ≤0.5) ranges between 2.6709–2.8648, and D3’ (fractal dimension of mini-micropores under high relative pressure, P/P0 >0.5) ranges between 2.6661–2.9256, indicating complex pore structures and rough surfaces. Mini-micropore accounts for the highest proportion of the total pores and its structure is mainly controlled by the abundance of organic matter. The pore structures of macropores and mesopores greatly influence the proportion of desorption gas in shale, while the structure of mini-micropores can control the maximum adsorbed gas volume of shale.